Draft Sixth Five Year Plan 1980-85 and Draft Annual Plan 1981-82 Scheme-Wise Details Union Territory of Pondicherry - Planning Commission (Planning Commission, 1980)
Pondicherry Union Territory consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another, Pondicherry region which is on the east coast, about 160 Kms, south of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is about 160 Kms. south of Pondicherry and it is surrounded Tanjavur district of Tamil Nadu. Yanam region is located about 650 Kms, north of Madras near Kakinada in Andhra Pradesh. Mahe region is on the west coast about 160 Kms. south of Mangalore, in Kerala.
Union Territory of Pondicherry